Surgical patients' perspectives on nurses' education on post-operative care and follow up in Northern Ghana - Bernard Atinyagrika Adugbire; Lydia Aziato (BMC, 2018)
Abstract Background The purpose of the study was to explore surgical patients' experiences of discharge planning and home care in the Northern part of Ghana. Methods The study was conducted at a referral hospital located at the Northern part of Ghana. A qualitative explorative descriptive design was adopted for the study. Purposive sampling technique was used to recruit participants. Data was saturated with 15 participants aged between 23 and 65 years. All the interviews were audio-taped and transcribed verbatim. Data analysis was done using the processes of content analysis. Results Nurses educated surgical patients on discharge to avoid smoking, alcohol drinking, chewing cola nuts and strenuous exercise to promote healing and prevent complications. Patients were educated to keep their wound dry and clean. Patients were advised to eat nutritious food, vegetables and fruits and take their medications as prescribed. They were to report drug effects and come to the hospital for follow-up visits. Patients were urged to come for daily wound dressing at the outpatient department. On the contrary, some nurses did not educate patients on signs of wound healing or infection. Some nurses were rude to the patients during wound dressing. Nurses did not visit patients at home when they were discharged from the hospital. Conclusions The study showed that although nurses were able to educate discharged patients on how to manage their health at home, there is the need to improve communication and attitude to enhance care.